Internalization of Higher Level Thinking and TPACK in the Science and Technology Teaching Module for Fourth Grade Elementary School Teachers in Pontianak within the Independent Curriculum Framework - Kartono, Kartono (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2024)
This research aims to describe the results of the internalization of higher order thinking and TPACK in the science and science subject teaching modules for fourt grades teachers in Pontianak elementary schools within the framework of the independent curriculum. This research uses a qualitative approach with descriptive methods. Qualitative descriptive research will produce descriptive data in the form of words. For research techniques, use manuscript documentation techniques. The results obtained in this research are in the form of independent curriculum teaching module components developed by the fourth grade homeroom teacher at an elementary school in Pontianak. The independent curriculum consists of general information, core components and complete attachments. Based on further research, it was found that teachers had included and implemented higher level thinking along with TPACK in the teaching modules used in learning. Thus, it can be said that teachers have implemented it in learning specifically within the framework of the independent curriculum.